Heat transfer enhancement in a tube heat exchanger with a v-shape winglet turbulator - Chokphoemphun, Suriya; Chompookham, Teerapat; Promvonge, Pongjet (Asia-Pacific Journal of Science and Technology, 2017)
This work presents the effect of V-Shape winglet vortex generators on heat transfer and thermal performance enhancement of a tube heat exchanger. The experiment was carried out in a uniform wall heat-fluxed tube by varying turbulent airflow for Reynolds number (Re) ranging from 5,300 to 24,000. In the present work, the winglet with three different attack angles (a=30 o , 45 o and 60 o ), three different winglet-height or blockage ratios (BR=e/D=0.1, 0.15 and 0.2) and four different winglet pitch ratios (PR=P/D=0.5, 1.0, 1.5 and 2.0) were inserted and placed in the core flow area into the test tube. The experimental results for the winglet at various parameters were evaluated and compared with those for the smooth tube alone. The measurement reveals that the winglet provides a considerable increase in the heat transfer and friction loss above the plain tube. The Nusselt number and friction factor increase with the increment of BR and Re but with decreasing the PR. The average Nusselt numbers for the winglet with various parameters are in the range of 1.40 - 2.43 times above the plain tube. The thermal performance for the parameter is found to be much higher than that unity and is in a range of 1.11-1.47, depending on the attack Re, แ, BR and PR values. The maximum thermal enhancement factor (TEF) for using winglet tabulators is 1.47 at Re = 5,300, a=30 o , BR = 0.1 and PR = 1.5 in this experiment.